Analisis Keterampilan Berpikir Kritis Siswa SMP pada Materi Sistem Kehidupan Tumbuhan - Purwanti, Elly (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The purpose of this study was to describe students’ critical thinking skills in the material of plant life systems. This research was conducted at SMP Negeri 16 Malang for the 2022/2023 school year. This research is a descriptive research. The research sample used 35 students consisting of 20 boys and 15 girls. The research instrument uses a test of critical thinking skills which consists of 5 essay questions. Students’ critical thinking skills are measured based on five aspects, namely: 1) giving simple explanations; 2) build basic skills; 3) provide conclusions; 4) make further explanations; and 5) forecasting and integration. The results showed that overall the students’ critical thinking skills reviewed based on the five aspects were in the less category with a percentage of 57.5%. However, in several aspects such as making conclusions and making further explanations, they are in the high category. The results of this study have implications for the importance of innovation in learning to improve students’ critical thinking skills. Some learning innovations that can be used to improve students’ critical thinking skills can be through Problem Based Learning (PBL), inquiry learning models, or other relevant learning models.